Exchange Rate Pass-through to Inflation: Symmetric and Asymmetric Effects of Monetary Environment in Nigeria: Array - Adedokun, Adebayo; Ogbaekirigwe, Charles; Tiamiyu, Kehinde (Acta Universitatis Danubius. Œconomica, 2022)
This study investigates symmetric, asymmetric, and structural models of exchange rate pass-through to inflation in Nigeria over the monthly period of 2000: Month 01- 2021: Month 05. The percentage change in the price of import-competing goods (traded goods) that is ascribed to a particular percentage change in the exchange rate (which is the price of one country's currency in terms of another country's currency) is referred to as exchange rate pass-through. This paper is set out to examine the impact of monetary environment in exchange rate pass-through to inflation in Nigeria using monthly time series data. The method adopted included inter-alia the use of both the Augmented Dickey-Fuller (ADF) unit root test and the Breaking point unit root test for relative comparison. The results of unit root tests from both ends indicate the existence of both stationary and non-stationary variables which made adoption of bounds cointegration test plausible and Nonlinear Autoregressive Distributed Lag(NARDL) methodologies applicable, this method allows the incorporation of possible asymmetric effects of positive and negative changes in explanatory variables on dependent variable unlike the conventional Autoregressive Distributed Lag (ARDL) models where the possible impact of explanatory variable changes remain unaccounted for on dependent variable. Further, the results from cointegration test confirm the existence of short-run situations among the variables of interest in all the models considered. Also, three models were estimated under the framework of linear and nonlinear Autoregressive Distributed Lag (ARDL) models. The model estimate findings revealed that inflation modeling in Nigeria is both autoregressive and adaptive in character. In the short run, pass-through estimates are larger, though declining, due to asymmetric behaviours of exchange rate changes as confirmed by Wald test. This justifies the existence of asymmetric effect in the behavour of exchange rate over times. It was also discovered that inflation is seldom a monetary occurrence in this new normal as industrial production index was found to reduce consumer prices drastically and exchange rate found to explain inflation better than money supply. However, structural policy of land border closure exerts positive but insignificant pressure on inflation in Nigeria during the period under investigation, this may be because of lag effect between the policy stance and reaction of economic agents in the economy. Finally, by policy recommendation, Nigerian government is thus advised to invest heavily in productive sectors of economy, specifically, by building capacities of local producers.